GG Polymorphism of Platelet ITGA2B Gene Increases the Magnitude of Interleukin-6 Release after Cardiopulmonary Bypass - Koray Ak; Samet Ergun; Hilal Altınoz; Z Oya Uyguner; Sermin Tetik (Imaging Journal of Clinical and Medical Sciences - Peertechz Publications, 2016)
Objective: Cardiopulmonary bypass (CPB) induces a systemic inflammatory response which is thought to be a significant cause of postoperative organ dysfunction and mortality. In this study we aimed to investigate the effect of ITGA2B (integrin alpha 2b, platelet glycoprotein IIb of IIb/IIIa complex) gene polymorphism on the magnitude of inflammatory response after CPB Methods: Twenty patients undergoing coronary artery bypass grafting were included. Blood samples were taken at the three different times for analyses of Interleukin-6, Interleukin-10 and Nuclear Factor Kappa B by ELISA (t1: before operation, t2:10 minutes after removal of aortic cross clamping and t3: 24 hours after operation. ITGA2B gene polymorphisim, c.2621T>G, resulting missense alteration, p.Ile874Ser (rs5911) was studied in patients and 27 healthy volunteers by targeted polymerase chain reaction (PCR) and restriction enzyme digestion. Perioperative organ dysfunction was evaluated by cardiac surgery scorring (CASUS) system. Results: There was no perioperative mortality. The mean ages of the patients and the controls were 67.45±12.30 and 51,38±7,03 years, respectively (p=0.001). Thirty-five percent (n=7) of the patients revealed TT, 45% (n=9) TG and 20% (n=4) GG polymorphism. The allele frequencies of the study group were similar to the controls (33,3%, n=9 revealed TT, 55,5 %, n=15 TG and 11,3%, n=3 GG). There was no significant difference in the frequency of genetic polymorphism between the patients and the controls. In the study group, patients with GG allele had signifi cantly higher interleukin 6 levels 24 hours after operation than the others (GG (338,14±22.20pg/ml) versus TT (306,14±22, 10 pg/ml), p=0.025, and GG versus TG (308, 12±14,50pg/ml), p=0.039).  Conclusion: Our results reveal that GG allele of ITGA2B gene might have a significant role in the magnitude of the inflammatory response after CPB.